2016
DOI: 10.1123/jsr.2014-0266
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Dynamic Elastomeric Fabric Orthosis in Supporting the Management of Athletic Pelvic and Groin Injury

Abstract: Context:Athletic pelvic and groin injuries are a common yet challenging problem. Pelvic belts have been successfully used to reduce pain and improve function but are not a practical solution for athletes. Therefore, there is scope to explore the use of a more dynamic intervention developed to aid in the management of this type of injury.Objectives:To undertake a preliminary investigation into the effectiveness of a dynamic elastomeric fabric orthosis (DEFO) in supporting the management of athletic pelvic and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…One component of a multimodal approach may be the use of dynamic elastomeric fabric orthoses (DEFO) or compression garments [19,24,25,26]. Commercial manufacturers have used previously reported research on this topic to design specific compression garments that target women in the prenatal and the postnatal periods with the objective of increasing wear-compliance based on the improved aesthetics and comfort of the DEFO garments in addition to their targeted design to provide support during functional activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One component of a multimodal approach may be the use of dynamic elastomeric fabric orthoses (DEFO) or compression garments [19,24,25,26]. Commercial manufacturers have used previously reported research on this topic to design specific compression garments that target women in the prenatal and the postnatal periods with the objective of increasing wear-compliance based on the improved aesthetics and comfort of the DEFO garments in addition to their targeted design to provide support during functional activity.…”
Section: Introductionmentioning
confidence: 99%
“…Sawle et al (2016) [26] discussed the concept of DEFO in pregnancy and postpartum as an intervention tool to manage common musculoskeletal conditions. Specifically, DEFO are thought to address common musculoskeletal conditions in women during pre and postnatal periods through a consistent applied force from customized and precisely positioned elastomeric panels that stabilize joints around the pelvic girdle, allowing for increased function whilst wearing the DEFO garment [26]. However, research examining the effectiveness, the feasibility, and the acceptability of DEFO to achieve these outcomes during pregnancy and in the postnatal phase is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This may in turn lead to a reduction of pain 32 . Secondly, compression shorts contribute to increased pelvic stability 29 . A cadaver study showed that a pelvic belt increased pelvic stability by reducing movement in the sacroiliac joints 39 , and in athletes with adductor-related groin pain the use of a pelvic belt significantly reduced pain during forceful isometric hip adduction in 68% 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Such stabilization may facilitate a possible improvement in pain enabling women to have better functional capacity while wearing the DEFO. 15,[20][21][22] Commercial manufacturers have considered previously published research regarding compression garments in postnatal care and DEFO in other populations. That has resulted in the development and design of specific compression garments to address the associated common ailments and/or conditions that women suffer in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%